Spatial analysis : a guide for ecologists - Fortin, Marie-Josée, 1958- (Cambridge University Press, 2005)
This book gives an overview of the wide range of spatial statistics available to analyse ecological data, and provides advice and guidance for graduate students and practising researchers who are either about to embark on spatial analysis in ecological studies or who have started but are unsure how to proceed.